1999
DOI: 10.1017/s0373463399008395
|View full text |Cite
|
Sign up to set email alerts
|

Differential Equation of a Loxodrome on a Sphere

Abstract: A curve that cuts all meridians of a rotating surface at the same angle is called a loxodrome. If the shape of the Earth is approximated by a sphere, then the loxodrome is a logarithmic spiral that cuts all meridians at the same angle and asymptotically approaches the Earth's poles but never meets them. Since maritime surface navigation defines the course as the angle between the current meridian and the longitudinal direction of the ship, it may be concluded that the loxodrome is the curve of the constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 1 publication
1
13
0
Order By: Relevance
“…If we take λ = 0 in Equation (16), we find the general solution of the differential equation of the loxodrome on rotational surface as follows where ε = ± 1. This equation coincides with the equation in (Noble, 1905; Kos et al, 2009).…”
Section: Differential Equation Of the Loxodromesupporting
confidence: 82%
See 3 more Smart Citations
“…If we take λ = 0 in Equation (16), we find the general solution of the differential equation of the loxodrome on rotational surface as follows where ε = ± 1. This equation coincides with the equation in (Noble, 1905; Kos et al, 2009).…”
Section: Differential Equation Of the Loxodromesupporting
confidence: 82%
“…Noble (1905) and Kos et al (2009) found the differential equation of the loxodrome on a rotational surface. If we take λ = 0 in Equation (16), we find the general solution of the differential equation of the loxodrome on rotational surface as follows where ε = ± 1.…”
Section: Differential Equation Of the Loxodromementioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the loxodromes are a popular topic in navigation, see [1] and [12]. From mathematical point of view, geometers have studied loxodromes defined on different kind of surfaces in various ambient spaces and then many works have been found in literature such as [11,15,13,9,5,6,7,10,16].…”
Section: Introductionmentioning
confidence: 99%